2008
DOI: 10.1016/j.jmps.2007.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Atomistically informed dislocation dynamics in fcc crystals

Abstract: We develop a nodal dislocation dynamics (DD) model to simulate plastic processes in fcc crystals.The model explicitely accounts for all slip systems and Burgers vectors observed in fcc systems, including stacking faults and partial dislocations. We derive simple conservation rules that describe all partial dislocation interactions rigurosuly and allow us to model and quantify cross-slip processes, the structure and strength of dislocation junctions and the formation of fcc-specific structures such as stacking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
89
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 55 publications
1
89
0
Order By: Relevance
“…The stress was applied along the Burgers vector direction, at a strain rate of 10 9 s −1 and a temperature of 300 K. Figure 6[a] shows the stress-strain curve for both the thin film and bulk systems. In bulk, in the absence of strong pinning points, screw dislocations in Cu move freely under phonon damping control since their Peierls barrier is small 22 . However, the presence of the constriction modifies this picture significantly.…”
Section: Response To Shear Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…The stress was applied along the Burgers vector direction, at a strain rate of 10 9 s −1 and a temperature of 300 K. Figure 6[a] shows the stress-strain curve for both the thin film and bulk systems. In bulk, in the absence of strong pinning points, screw dislocations in Cu move freely under phonon damping control since their Peierls barrier is small 22 . However, the presence of the constriction modifies this picture significantly.…”
Section: Response To Shear Loadingmentioning
confidence: 99%
“…The core energy is empirically represented by a linear core cutoff for adjacent segments as in the Paradise code 21 . The interfacial free energy of the intrinsic faults is also included 22 . The energies are listed in Table I 15 , it has a lower energy than the straight dislocation [a].…”
Section: Introductionmentioning
confidence: 99%
“…1,3 However, Madec and co-workers 7 reported that the interaction between two intersecting dislocations with collinear Burgers vectors is the strongest of all dislocation reactions. Previous modeling and simulations [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] on investigating the dislocation intersections emphasized the importance of the interaction details between individual dislocations, including not only the long-range elastic interactions but also the short-range core reactions. Most of these researches suggested that the dislocation interactions can be studied by multiscale approaches, where the discrete dislocation dynamics (DDD) based on continuum elasticity theory deals with the long-range elastic attraction or repulsion, and atomistic simulations the short-range reaction rules.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these researches suggested that the dislocation interactions can be studied by multiscale approaches, where the discrete dislocation dynamics (DDD) based on continuum elasticity theory deals with the long-range elastic attraction or repulsion, and atomistic simulations the short-range reaction rules. 9 Different from the DDD techniques that require priori rules as inputs, 10 another simulation method also based on continuum elastic theory called phase field model (PFM) [25][26][27][28][29][30] can straightforwardly account for the effects of short-range core reactions by incorporating the generalized stacking fault energy (γ-surface) 11 from atomistic or first principle calculations, such as dislocation dissociation. [31][32][33][34][35] With this advantage, the PFM model of dislocation shows great potential in modeling dislocation intersections.…”
Section: Introductionmentioning
confidence: 99%
“…We will not discuss the resistance of relatively short LCjunctions against unzipping, generally found in dislocation dynamics simulations. [9][10][11] and investigated with atomic models [12,13]. We rather consider the resistance which a long LC lock exerts against an approaching screw dislocation.…”
mentioning
confidence: 99%